ANALYSIS OF THE IMPLEMENTATION OF ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) IN IMPROVING POLICE PERFORMANCE AND PUBLIC COMPLIANCE WITH TRAFFIC REGULATIONS AT THE TRAFFIC DIRECTORATE OF THE SOUTH SULAWESI REGIONAL POLICE - Syaifullah Yusran; Muhammad Nasir Hamzah; Muh.Ashary Anshar (International Journal of Multidisciplinary Research and Literature, 2026)
This study aims to analyze the implementation of Electronic Traffic Law Enforcement (ETLE) in improving police performance and public compliance in traffic at the Traffic Directorate of the South Sulawesi Regional Police. This study uses a qualitative method with an explanatory case study approach to gain a deep understanding of the implementation of ETLE as a digital innovation in traffic law enforcement. Research data were obtained through interviews, observations, and documentation with seven informants consisting of police officers, ETLE operators, members of the public who have been caught violating ETLE, and academics in the field of transportation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of ETLE has been effective in supporting a more modern, transparent, and accountable traffic law enforcement process. The use of electronic camera technology and the integration of motor vehicle databases can increase the effectiveness of supervision, accelerate the process of identifying violations, and strengthen the professionalism of police performance. In addition, ETLE has a positive impact on changing public behavior by increasing discipline in complying with traffic regulations and creating a deterrent effect for violators. However, the implementation of ETLE still faces several obstacles, such as the limited number of surveillance cameras, network system disruptions, and less than optimal socialization to the public. This study concludes that ETLE is an effective digital transformation strategy in strengthening police performance and increasing public legal awareness in creating a culture of orderly traffic.